PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PETUGAS KESEHATAN DALAM PENANGGULANGAN KANKER PAYUDARA TAHAP DETEKSI DINI - Rosita Rosita; I Made Christian Binekada; Adius Kusnan (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Cancer, one of the diseases included in the group of non-communicable diseases (NCD) is the biggest cause of death in the world, the death rate due to NCD is higher than the total number of deaths due to other causes. The purpose of the study was to analyze the effect of work motivation, work discipline, and leadership style on the performance of health workers in the early detection stage of breast cancer. This type of research is descriptive observational using a cross sectional design. This study involved 45 health workers in 15 health centers throughout Kendari City. Data analysis using chi square test and logistic regression using SPSS software version 16.0, where the test results with p-value <0.05 are considered significant. The results showed that the performance of health workers in the management of breast cancer in the early detection stage was related to work motivation (0.025), leadership style (0.003), while the work discipline variable was not related (0.227). The results of multivariate analysis showed that the most related p-value was leadership style with p=0.003. From this research it can be concluded that leadership style is very dominant related to the performance of health workers.